Development of a two-species interaction sub-module for the ILCYM platform - Carhuapoma, Pablo; Gamarra, H.; Kreuze, J.F. (2025)
This report presents a new two-species interaction sub-module for the ILCYM platform, which integrates temperature-dependent thermal functions of pests and natural enemies into a coupled mechanistic framework. The model generates innovative ecological indices—Parasitism Synchrony Index (PSI), Temporal Suppression Ratio (TSR), and Biological Control Efficiency (BCE)—and enables interactive simulations to optimize the selection, timing, and deployment of biological control agents. Validated with relevant case studies (Tecia solanivora–Copidosoma koehleri, Bemisia tabaci–Encarsia tabacivora, Bactericera cockerelli–Tamarixia triozae), this work aligns strongly with Regenerative Agriculture, Resilient Agrifood Systems, and Climate-smart Agriculture, making it a strategic tool for integrated pest management under climate change.